Identification of Genes Interacting with rnt-1 Through Large-Scale RNAi Screening in Caenorhabditis elegans - Lee, Kiho (Genetics Society of America, 2013)
Although many critical roles of the RUNX family proteins have already been identified, little attention has been given to how these proteins interact with other factors. Elucidating RUNX protein interactions will help extend our understanding of their roles in normal development and tumorigenesis. In this study, we performed large-scale RNAi screening to identify genes that genetically interact with rnt-1, the sole homolog of RUNX protein in the nematode Caenorhabditis elegans. To this end, we took advantage of the fact that C. elegans can survive a severe loss of RNT-1 function with only mild phenotypes, and we looked for genes that caused a synthetic phenotype in the rnt-1 mutant background. We identified seven genes, three of which (cdk-8, cic-1, and sur-2) are involved in transcription, two of which (pgp-2 and cct-5) are involved in stress response, and two of which (D2045.7 and W09D10.4) are involved in signaling cascades, according to their functional gene ontology terms. We further confirmed that the CDK8-containing mediator complex genetically interacts with RNT-1 by showing that knockdown of each component of the CDK8 mediator complex caused a synthetic phenotype, that is, the exploded intestine through the vulva (Eiv) phenotype, in the rnt-1 mutant background. We also identified a putative target gene, acs-4, which is regulated by the RNT-1 and CDK8 mediator complex. Our results strengthen the notion that the CDK8 mediator complex may also act together with RUNX proteins in mammals.